Virginity Discourse from Netizen’s POV "PASANGAN HARUS PERAWAN/PERJAKA? Menurut Lu” in the IDN_Times’ YouTube Social Media Comment Section - Sarah Fibrianty Butarbutar (Journal of Feminism and Gender Studies, 2025)
Virginity is often associated with the hymen even though not all women are born with a hymen. Our society is often mistaken, and assumes that if a woman does not bleed when having sexual intercourse for the first time, it means she is no longer a virgin. Our society still adheres to a high patriarchal culture, there are different views related to the discourse of virginity between women and men, women who are not virgins are considered to have no morals and are ostracized in the family and community environment. The purpose of this research is to see how netizens interpret the virginity discourse in the comments column on IDN_Times YouTube social media. This research uses a qualitative approach method. This research uses Kozinets netnography research method. The result is that non-virgin women are considered cheap, given a negative stigma by netizens, especially men, non-virgin women get sexist comments such as prostitutes, cheap women, damaged women and trash women. Virginity is considered a valuable and important thing in society. The power of patriarchal culture influences conversations about virginity, making it an important factor in judging a woman's behavior. Non-virgin women are negatively stigmatized and ostracized from society, because they are considered a disgrace and shame, so they often experience rejection from their families and society. This is of course different if the man is not a virgin, the community generally will not give a negative stigma and consider it as something ordinary and normal.